(untitled) (Conference Zone, 2022)
This paper presents a model of the interaction between corrupt government officials and industrial firms to show that corruption is antithetical to competition. It is hypothesized that a government agent that controls access to a formal market has a self-interest in demanding a bribe payment that serves to limit the number of firms. This corrupt official will also be subject to a detection technology that is a function of the amount of the bribe payment and the number of firms that pay it. Under quite normal assumptions about the shape of the graph of the detection function, multiple equilibria can arise where one equilibrium is characterized by high corruption and low competition, and another is characterized by low corruption and high competition. Some suggestive empirical evidence is presented that supports the main hypothesis that competition and corruption are negatively related.